Multi-objective methods for crop insurance premiums: framework proposal and a case study in sugarcane - Silva, Roberto F.; Benso, Marcos R.; Gesualdo, Gabriela C.; Mendiondo, Eduardo M.; Saraiva, Antônio M.; Marques, Patrícia A. A.; Delbem, Alexandre C. B. (Anais do Congresso Brasileiro de Agroinformática (SBIAGRO), 2021)
The increase in extreme climate events due to climate change has resulted in crop losses, quality losses, environmental and social impacts in agricultural areas. Insurance against extreme events is a vital tool adaptation to deal with the impacts of those hazards. However, few works consider the optimization of different dimensions related to this tool. This work proposes a framework to use multi-objective optimization models to better design and evaluate crop insurance premiums and conducts a case study for sugarcane premiums at São Paulo state in 2010. The framework can be adopted for different crops, objectives, and models. The case study showed that around 20% of the policies evaluated were efficient solutions from the farmer's point of view.